A dimer model of human calcitonin13‐32 forms an α‐helical structure and robustly aggregates in 50% aqueous 2, 2, 2‐trifluoroethanol solution. (30th May 2016) - Kawashima, Hiroyuki; Katayama, Mei; Yoshida, Ryota; Akaji, Kenichi; Asano, Akiko; Doi, Mitsunobu
Abstract : Determining the cause of human calcitonin (hCT) aggregation could be of help in the effort to utilize hCT for treatment of hypercalcemia. Here we report that a dimer model of hCT13‐32 aggregated to a greater degree than native hCT under aqueous 2, 2, 2‐trifluoroethanol conditions. Analyses using circular dichroism spectroscopy, thioflavine‐T binding assays and atomic force microscopy suggest that the α‐helical portion of hCT is important for initiation of the aggregation process, which yields long fibrils. Dimerization, which stabilizes the β‐sheet structure of hCT, enhances aggregation potency. Dimerization of hCT stabilizes the α‐helix under aqueous TFE conditions, leading to the long fibril formation. Up to now, there have been no reports of using a dimer model to investigate the properties of hCT aggregation. Our findings could potentially serve as the basis for development of novel hCT derivatives that could be utilized for treatment of hypercalcemia, as well as for development of novel therapeutics for other ailments caused by amyloid peptides. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : We report that a dimer model of human calcitonin13‐32 (hCT13‐32) aggregated to a greater degree than native hCT under aqueous TFE conditions. Analyses using circular dichroism spectroscopy, thioflavine‐T binding assays and atomic force microscopy suggest that the α‐helical portion of hCT is important for initiation of the aggregation process, which yields long fibrils. Our findings could potentially serve as the basis for development of novel hCT derivatives that could be utilized for treatment of hypercalcemia.